Nanoscale Noncollinear Spin Textures in Thin Films of a D2d Heusler Compound. Issue 32 (3rd July 2021) - Sharma, Ankit K.; Jena, Jagannath; Rana, Kumari Gaurav; Markou, Anastasios; Meyerheim, Holger L.; Mohseni, Katayoon; Srivastava, Abhay K.; Kostanoskiy, Ilya; Felser, Claudia; Parkin, Stuart S. P.
Abstract: Magnetic nano‐objects, namely antiskyrmions and Bloch skyrmions, have been found to coexist in single‐crystalline lamellae formed from bulk crystals of inverse tetragonal Heusler compounds with D 2d symmetry. Here evidence is shown for magnetic nano‐objects in epitaxial thin films of Mn2 RhSn formed by magnetron sputtering. These nano‐objects exhibit a wide range of sizes with stability with respect to magnetic field and temperature that is similar to single‐crystalline lamellae. However, the nano‐objects do not form well‐defined arrays, nor is any evidence found for helical spin textures. This is speculated to likely be a consequence of the poorer homogeneity of chemical ordering in the thin films. However, evidence is found for elliptically distorted nano‐objects along perpendicular crystallographic directions within the epitaxial films, which is consistent with elliptical Bloch skyrmions observed in single‐crystalline lamellae. Thus, these measurements provide strong evidence for the formation of noncollinear spin textures in thin films of Mn2 RhSn. Using these films, it is shown that individual nano‐objects can be deleted using a local magnetic field from a magnetic tip and collections of nano‐objects can be similarly written. These observations suggest a path toward the use of these objects in thin films with D 2d symmetry as magnetic memory elements. Abstract : Noncollinear magnetic nano‐objects are observed in epitaxial thin films of the D 2d Heusler compound Mn2 RhSn using magnetic force microscopy. The nano‐objects are stabilized over a wide temperature‐field region and can be deleted or created by local magnetic fields, thereby paving a path toward the realization of skyrmionic devices based on D 2d Heusler thin films.